A Longitudinal Historical Population Database in Asia. The Taiwanese Historical Household Registers Database (1906–1945) - Chia-chi Lin; Shu-juo Chen; Ying-chang Chuang; Wen-shan Yang; James Wilkerson; Ying-hui Hsieh; Ko-hua Yap; Yu-lin Huang (Historical Life Course Studies)
For the past 35 years, the Taiwan Historical Household Registers Database (THHRD) has been significant for historical demographic research on Asia. In recent years, researchers have continued adding new demographic information to the database. This allows for the expansion of research on the topic of historical households in the region. However, there are still many issues to address in the field of Asian historical demography. This paper provides a brief introduction on the uses of THHRD for future research.